Integrating Spinoza’s Philosophy of Civil Law into Indonesian Judicial Reasoning: Toward a Justice-Oriented Legal Framework - Susilo, Erwin (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2024)
Previous studies on Spinoza have generally focused on his political and theological philosophy, while the application of his concept of civil law in judicial decision-making practice has been rarely discussed, creating a research gap in the context of its application to modern legal systems. This research aims to integrate Spinoza's philosophy of civil law—rooted in rationality, equality, and moral order—into the framework of judicial consideration in Indonesia, where the balance between positive law and justice remains challenging. Using a normative juridical method with statutory, comparative, and conceptual approaches, this research examines relevant legal provisions and comparative practices from democratic countries such as the United States, France, Germany, India, and New Zealand, as well as the philosophical foundations of Spinoza's thinking on civil law and justice. The research findings indicate that Spinoza's view of law as a rational agreement based on moral necessity aligns with the principles of freedom, equality, and human dignity in the Indonesian Constitution. Integrating this idea into legal considerations can guide judges to move beyond formalistic interpretations towards justice oriented towards morality and humanity. Theoretically, this research contributes by offering a philosophical framework for rational legal reasoning, while practically providing a model for balancing legal certainty with moral justice in judicial practice and law enforcement in Indonesia.